Innate immunity in cutaneous melanoma. (1st April 2017) - Mignogna, C.; Scali, E.; Camastra, C.; Presta, I.; Zeppa, P.; Barni, T.; Donato, G.; Bottoni, U.; Di Vito, A.
Summary: The skin immune system is composed of a vast network of immune cells, including lymphocytes, macrophages, neutrophils, dendritic cells and Langerhans cells, which not only are involved in inflammatory responses but also contribute to homeostatic function and may participate in the various steps of carcinogenesis. Many studies support the notion that innate immunity has a key role in the development, growth and prognosis of cutaneous malignant melanoma (MM), through the release of pro‐ and/or anti‐inflammatory cytokines and tumour growth factors. The tumour environment in a major subset of cutaneous MM shows evidence of a T cell‐infiltrated phenotype, but there is less known about the presence and the phenotype of other immune system cells. Response to immunotherapy is largely correlated with the presence of T cells in the tumour microenvironment, while the regulation exerted by stromal components such as macrophages and mast cells has been less investigated. In the current report, we review the recent literature, focusing our attention on the role of macrophages, dendritic cells, mast cells and natural killer cells in orchestrating MM progression, to better understand tumour immunobiology. The identification of new therapeutic targets and the application of approaches aimed at modulating crosstalk between immune and tumour cells, could have a crucial impact on immunotherapy and result in better clinical outcome. We hope this review will be helpful in cutaneous MM research. Abstract : Click here for the corresponding questions to this CME article.